Investigation of spin waves in metallized magnonic crystal - V. V. Vitko (Известия высших учебных заведений России: Радиоэлектроника, 2016)
Theoretical model for the ferrite spin-wave magnonic crystals has been developed. A considered magnonic crystal has a construction of periodically metallized thin ferrite film. An influence of various magnonic crystal parameters on its transmission-loss characteristic was analyzed. It is shown that a developed model described with high accuracy the microwave transmission-loss characteristics.